Changes of children's physical activity from 1st to 4th grade are related to parents' educational level and Family Health Climate: a longitudinal study with primary school-aged children - Ziegeldorf, Alexandra; Niermann, Christina; Speer, Andreas; Streicher, Heike; Wagner, Petra; Wulff, Hagen (Frontiers in Sports and Active Living, 2025)
IntroductionDespite the well-known health benefits of physical activity, 81% of adolescents are physically inactive. Overall, studies showed that physical activity decreases with age during childhood and from childhood to adolescence. However, physical activity does not change uniformly for all children, the changes differ inter-individually. There are several studies that examine correlates and predictors of different patterns of change. However, studies focusing on family environmental factors are rare. The current study examines the relevance of two types of family environmental influences—parents' educational level and the Physical activity related Family Health Climate—for physical activity change patterns from first to fourth grade in primary school.MethodsLongitudinal data sets from the KOMPASS(2) study (n = 497) were used for analyses. Parents' educational level, Family Health Climate and children's overall physical activity as well as their engagement in organized sports were measured using parent questionnaires. Four groups were formed to map patterns of change for both children's overall physical activity and for their engagement in organized sports (1st to 4th grade): (1) no/not enough engagement at both time points, (2) a change from no/not enough engagement to (enough) engagement, (3) a change from (enough) engagement to no/not (enough) engagement and (4) (enough) engagement at both time points. Data were analyzed using multinomial logistic regression.ResultsMore than half of the children (53.5%) were in the pattern “continuously insufficient physical activity”, with a higher proportion of girls. For participation in organized sport, most children (56.1%) were assigned to the “continuous organized sport” pattern of change. Results showed differences in overall physical activity patterns according to parents' educational level and children's sex. Girls and children with highly educated mothers had an increased risk of being continuously physically inactive over the course of primary school. Organized sport patterns are related to parents' educational level and Family Health Climate. Children with higher educated parents and a higher Family Health Climate score had a lower risk of not being active in organized sport.DiscussionThe study investigated characteristics of different patterns of physical activity change from 1st to 4th grade during primary school. It highlights the importance of differentiating between different types of physical activity as children's sex, parents' educational level and the Family Health Climate predicted overall physical activity and organized sports participation in different ways. This is the first study focusing on change patterns during primary school and stresses previous findings of an early decline of physical activity. The results indicate that the entry in the educational system might be a good time to start with interventions.